Persepsi Guru Sekolah Dasar Terhadap Penerapan Pembelajaran Literasi Numerasi Pada Kurikulum Merdeka - Ayu Nurmala; Ika Fitriana Sasmita Sari; Noriko Vika Prasetyono; Selvi Novianti; Tia Citra Bayuni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Teacher perception is a key factor influencing curriculum implementation in elementary schools, particularly in the application of numeracy literacy learning in the Independent Curriculum. This study aims to describe elementary school teachers’ perceptions of numeracy literacy and the implementation of the Independent Curriculum in their educational environment. Numeracy literacy is defined as a teacher’s ability to use symbols and numbers to solve practical problems, analyze information presented in form of graphs, tables, or diagrams, and interpret it to make appropriate decisions. The research method used is quantitative descriptive with a Likert-scale-based survey instrument distributed to elementary school teachers in certain areas. The results are expected to provide a comprehensive picture of the level of understanding, attitudes, and challenges faced by teachers in implementing literacy according to the direction of the Independent Curriculum. These findings will form the basis for developing professional teacher training, developing learning modules, and policies that are more responsive to the needs of teachers and students. Thus, this research not only provides academic but also practical contributions in improving the quality of mathematics learning and numeracy literacy in elementary schools.